2016
DOI: 10.1016/j.rhm.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with caesarean sections in Phnom Penh, Cambodia

Abstract: C-sections are an increasingly performed medical practice which can save lives but may also lead to major complications. Through a mixed methods study conducted in 2015 in Cambodia, we aimed to analyze the reasons for requesting a c-section and to explore factors that are associated with c-sections. 60% of the women in the cohort who gave birth by c-section reported having requested it. Through 31 in-depth interviews, we determined the reasons given by women for requesting a c-section before and during labour.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 28 publications
5
50
0
1
Order By: Relevance
“…Most of these social factors identified in our study were commonly observed across multi-countries worldwide: fear of childbirth [14,[22][23][24][25][26][27][28], lack of self-efficacy for childbirth [22,29,30], and belief that CS is superior to vaginal delivery [10,14,[31][32][33], wealthier family [7,13], and private hospital [14,34]. Additionally, determinants of decision making such as a belief that CS is a part of a woman's autonomy [10,14,35], the strong impact by media [19,36], and/or family and friends [14,19,22,29,37] are consistent with previous studies.…”
Section: Social Factors For Increased Csmentioning
confidence: 80%
“…Most of these social factors identified in our study were commonly observed across multi-countries worldwide: fear of childbirth [14,[22][23][24][25][26][27][28], lack of self-efficacy for childbirth [22,29,30], and belief that CS is superior to vaginal delivery [10,14,[31][32][33], wealthier family [7,13], and private hospital [14,34]. Additionally, determinants of decision making such as a belief that CS is a part of a woman's autonomy [10,14,35], the strong impact by media [19,36], and/or family and friends [14,19,22,29,37] are consistent with previous studies.…”
Section: Social Factors For Increased Csmentioning
confidence: 80%
“…19,26,33 In some settings, there are perceived advantages for the child of an auspicious birthdate. 18,24,28,34 Previous negative experiences of vaginal birth, including suboptimal quality of care, and experiences of disrespect and abuse, also influence choice for CS birth in subsequent pregnancies. 23,[35][36][37] Contemporary society exposes pregnant women to a wide range of information on pregnancy and childbirth.…”
Section: Factors Related To Childbearing Women Families Communitiesmentioning
confidence: 99%
“…In settings where obstetricians combine public and private work, scheduling elective CSs allows for private work to be reconciled with public duties. 34,53,57 Factors related to healthcare systems, financial reimbursements, and organisational…”
Section: Factors Related To Health Professionalsmentioning
confidence: 99%
“…Similarly, a study using data from 29 countries in Asia, Africa and Latin America showed higher CS rates in urban areas than in periurban areas (18). Conversely, a study in Cambodia showed that CS rates were lower for women living in Phnom Penh than for women living in its surrounding area (19).…”
Section: Literature Review Relationship Between Cs and Place Of Residmentioning
confidence: 96%